Burden of cancer trial participation: A qualitative sub-study of the INTERIM feasibility RCT. (March 2023) - Nwolise, Chidiebere; Corrie, Pippa; Fitzpatrick, Ray; Gupta, Avinash; Jenkinson, Crispin; Middleton, Mark; Matin, Rubeta
Objective: A qualitative sub-study was carried out within a larger phase II feasibility trial, to identify and describe the burden experienced by advanced melanoma patients participating in a clinical trial and the factors affecting their capacity to cope with the burden. Methods: Semi-structured interviews were conducted with fourteen patients with advanced melanoma recruited from National Health Service hospitals in the United Kingdom. Qualitative analysis was undertaken using a framework analysis approach. Normalisation process theory was applied to the concept of research participation burden in order to interpret and categorise findings. Results: Burdens of participation were identified as arising from making sense of the trial and treatment; arranging transport, appointment and prescriptions; enacting management strategies and enduring side effects; reflecting on trial documents and treatment efficacy, and emotional and mental effects of randomisation and treatment side effects. Factors reported as influencing capacity include personal attributes and skills, physical and cognitive abilities and support network. Discussion: This is the first study to highlight the substantial burden faced by patients with advanced melanoma in a clinical trial and factors that may lessen or worsen the burden. Consideration of identified burdens during trial design and execution will reduce the burden experienced by research participants.